Transformasi Budaya Pendidikan Dayah di Aceh - Silahuddin Silahuddin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2015)
This research is motivated by the thought of how to develop an academic culture in the Islamic boarding school, because the Islamic boarding school is the first and oldest educational institutions for Muslims in Aceh. In the long history Dayah has tried to adapt so that it can exist up to now by maintaining traditional culture in accordance with the local culture, Islamic boarding school continues to grow and has produced many Islamic scholars and generations. But in this era of globalization existence dayah began to decrease, causing the decreasing interest of young people to study at Islamic boarding school, then one way to maintain it is to develop an academic culture in the Islamic boarding school that can still exist in education and teaching, and not eliminated with the development of globalization now, one way is to develop the academic culture., the academic culture that needs to be developed in the Islamic boarding school is like writing culture, culture of giving an opinion, developing a culture of scientific and cultural development of the organization so it can maintain its traditional dayah although in the era of globalization. The development of academic culture is an effort to build the values ​​and norms which featured academic atmosphere, the atmosphere appropriate values ​​and scientific principles in an effort to acquire and develop knowledge and seek the truth.